HUMAN IMUNODEFICIENCY VIRUS INFECTION IN PREGNANCY - Sparić, Radmila M.; Pavić, Aleksandra; Andrić, Luka; Novković, Aleksa; Tomašević, Đina; Pavić, Slađana (Srpski medicinski časopis Lekarske komore, 2023)
HIV infection represents one of the major global public health challenges, especially among women of reproductive age. In 2020, there were 1.3 million pregnant women infected with HIV worldwide. Untreated HIV infection in pregnancy carries an increased risk of maternal and perinatal morbidity and mortality. Perinatal transmission of HIV refers to the transmission of the virus from mother to child during pregnancy, childbirth, or puerperium. The aim of this paper is to present the up-to-date information on diagnosis, treatment, and monitoring of pregnancy in HIV-positive women, with reference to the time and mode of delivery, in order to prevent the transmission of the virus from mother to fetus. The main goals of monitoring and treating HIV infection during pregnancy are the following: preventing the transmission of the virus to the fetus, preserving the mother’s health, and providing conditions for a safe delivery. The goal of treatment is to maintain the lowest level of the virus in the blood, especially at the time of delivery, in order to reduce the risk of vertical transmission. It is recommended to start treatment of HIV infection before pregnancy. Also, regular monitoring of the viral load, the CD4+ lymphocyte count, and blood count, as well as performing liver and kidney function tests, is necessary. The choice of the time and mode of delivery should not differ in pregnant women with a low viral load, as compared to healthy pregnant women, while in pregnant women with a high viral load, the pregnancy should be ended with elective caesarean section. HIV infection affects both the pregnant woman and the fetus. Therefore, antenatal, intrapartum, and postpartum monitoring is important. The decision on therapy, as well as the time and mode of delivery, should be individual, and made in accordance with the viral load, the clinical presentation of HIV infection of the mother, and the condition of the fetus.